Theoretical Identification of the Factors Governing the Reactivity of C−H Bond Activation by Non‐Heme Iron(IV)‐Oxo Complexes. Issue 7 (26th June 2019) - Roy, Lisa
Abstract: Selective functionalization of C−H bonds provides a straightforward approach to a large variety of well‐defined derivatives. High‐valent mononuclear iron(IV)‐oxo complexes are proposed to carry out these C−H activation reactions in enzymes or in biomimetic syntheses. In this Minireview, we aim to highlight the features that delineate the distinct reactivity of non‐heme oxo‐iron(IV) motifs to cleave strong C−H bonds in hydrocarbons, primarily focusing on the hydrogen atom transfer (HAT) process. We describe how the structural and electronic properties of supporting ligands modulate the oxidative property of the iron(IV)‐oxo complexes. Furthermore, we highlight the decisive role played by spin‐state in these biomimetic reactions. We also discuss how tunneling and external perturbations like electric field influence the transfer of hydrogen atoms. Lastly, we emphasize how computations could work as a practical guide to sketch and develop synthetic models with greater efficacy. Abstract : Simplifying a complex problem : This Minireview identifies the factors that fine‐tune the reactivity and mechanism in C−H bond cleavage by non‐heme iron(IV)‐oxo complexes, such as electronic and geometrical structure of supporting ligands, spin state on metal centre, orbital interactions between approaching fragments, tunnelling, external electric field and othersidentified by theoretical analyses. A fine balance among all these features ensures an enhanced oxidation by Fe(IV), parallel to enzymatic catalysis.